Knowledge, Attitude and Practice on Menstrual Cups Among South Indian Students for Plastic and Chemical - Free Menstrual Hygiene - Suresh, Chenchu; K. Dharani , K. Dharani; S. Indumathi, S. Indumathi; Kiran Sai, Maccha.; Linganna, K. Raja; Naveen, Rayadurgam (Journal of Neonatal Surgery, 2025)
To Assess and promote the use of menstrual cups and develop and implement awareness campaigns to improve menstrual hygiene practices and sustainability among south Indian students. Method: A cross-sectional observational study conducted to assess the KAP of secondary school, undergraduate and graduate students in Ananthapuramu, south India. We have randomly selected 289 eligible students were given with a per-validated self-administered questionnaire menstrual cups among students for plastic and chemical - free menstrual hygiene Results: The mean age of the study population was 20.21 years. The study revealed that 86.5% of participants had heard about menstrual cups, indicating a high level of general awareness. However, only 62.9% of participants were aware of the material composition of menstrual cups. A majority of participants 73% reported that difficulty in inserting the menstrual cup was a reason for discontinuing its use. 63 % of agreed that menstrual cups are a more accessible option for menstrual hygiene, indicating a positive attitude toward availability and practicality and 76.8% reported that they would recommend the use of menstrual cups to others, indicating a positive perception and advocacy for this menstrual hygiene product. Conclusion: The level of awareness about menstrual cups is a considerable gap between knowledge, attitude, and actual practice. While most participants recognized the environmental and health benefits of menstrual cups and expressed a positive attitude toward their use.